Contemporary Irish Women Poets : Memory and Estrangement. - Collins, Lucy. (Liverpool English Texts and Studies, 2015)
Original study of contemporary women poets in Ireland, presenting readings of four important poets (Eavan Boland, Eiléan Ní Chuilleanáin, Mairéad Byrne and Vona Groarke) and exploring themes and patterns in contemporary Irish women's poetry.